Legal analysis of construction defect claims within common law jurisdictions for Malaysia / Teng Kam Wah - Teng, Kam Wah (2018)
This research focuses on the legal perspectives of some selected issues of construction defect claims in three areas: causes of action, remedies and limitation periods. There are certain issues pertaining to construction defect claims in Malaysia where the law is unsettled, or where application of the law leads to unfairness or injustice, or where the applicable legal principles do not fit neatly into the broader conceptual framework of the law. This study aims to propose the most appropriate judicial and legislative responses to the law on construction defect claims in Malaysia with particular focus on areas which are still mired in controversy or are still developing. The research methodology is doctrinal research. Doctrinal legal research is an endeavour predominantly concerned with the analysis of legal principles and the manner in which they have been developed and applied. The primary sources of information are court decisions, statutes and standard forms of construction contract. The secondary sources are journal articles, books, conference and seminar papers, theses, dissertations and online resources. The significance and contribution of the research include providing recommendations on the proper approaches to take to resolve controversial or difficult issues in construction defect claims and thus reducing disputes in the construction industry and promoting greater harmony amongst all the various parties and consequently, at the macro level, contributing to the healthy and orderly growth of the construction industry. The research also provides some recommendations on whether there is a need for legislative intervention in the interest of social justice for construction defect claims. This research recommends that where loss is suffered by the owner who is not the employer in a construction contract, the law should prevent the situation where neither the owner nor the employer can recover damages for the loss from the contractor. Where the parties involved in a construction project like the employer, main contractor, sub-contractors and architect have structured their respective liabilities by contract, the court should be slow to superimpose a duty of care which goes beyond the contemplation of the parties at the time of the making of the contracts. There should be no policy bar to claims for pure economic loss for defective buildings. There should be legislative intervention to impose on builders and others involved in the provision of houses the obligations of a transmissible warranty of the quality of their work and the fitness for occupation of the completed houses. Under certain circumstances, it may be appropriate to assess damages to the aggrieved employer on the basis of the savings made by the contractor in the misperformance of his work. Damages for non-financial loss to the employer like loss of amenity, distress and inconvenience should be more readily available and should not invariably be modest in quantum. An order for specific performance to rectify construction defects ought to be granted by the court in appropriate circumstances. The law on the limitation period for latent defect claims in negligence should be amended to allow for limitation to run from the date when the fault is discovered, or at least discoverable.